Modern Approaches to Analysis of Technical and Tactical Actions of Skilled Volleyball Players - Iryna Oliinyk; Eduard Doroshenko; Mykhaylo Melnyk; Ruslana Sushko; Valeria Tyshchenko; Valerij Shamardin (OVS LLC, 2021)
Purpose. To develop an algorithm of special analysis for improving the training process, based on the identification of indicators of technical and tactical actions in the competitive activity of skilled volleyball players. Material and Methods. The study analyzed 2,688 technical and tactical indicators of the competitive activity of 56 players of national volleyball teams which played 6 games in the 2019 CEV Volleyball European Championship, taking into account the athletes' playing roles, based on the methods of analysis of the competitive activity, analysis of generalization of practical experience, and theoretical modeling. Results. The study interpreted the total performance indicators of the competitive activity of skilled volleyball players, the indicators of technical and tactical activity in the competitive process, the ratio of performance indicators in skilled volleyball players in position zones. Conclusions. The modified algorithm of special analysis of indicators of technical and tactical actions has the following structure: analysis of quantitative characteristics of team, group and individual actions in attack and defense; chronological analysis of the competitive activity development in sets; analysis of playing actions in various zones of the court; comparative analysis of quantitative indicators of technical and tactical actions of volleyball players who directly counteract in the match; analysis of critical moments of the game, which is directly related to organizing and holding a particular match; interpretation and qualitative analysis of indicators of technical and tactical actions in a particular match. Based on the analysis of success and performance indicators of the competitive activity of Ukraine's national volleyball team in the qualifying tournament of the 2019 European Championship (group F), it can be said that the modified algorithm of special analysis of indicators of technical and tactical actions showed high efficiency.